Interactive Media Use in Early English Vocabulary Learning: Penggunaan Media Interaktif dalam Pembelajaran Kosakata Bahasa Inggris Tingkat Awal - Ristha Octhavia; Yuli Astutik (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: English language learning at the elementary level plays an important role in developing early communication skills and literacy. Specific Background: Many young learners experience difficulties in understanding vocabulary due to limited use of engaging and interactive learning media. Knowledge Gap: Existing learning practices often lack integration of interactive technology that supports active student participation in vocabulary acquisition. Aims: This study aims to develop and apply interactive learning media to support English vocabulary learning for elementary students. Results: The findings indicate that the use of interactive media encourages student participation, supports understanding of word meanings, and creates a more engaging learning environment. Novelty: This study highlights the application of interactive technology-based media tailored for young learners in English vocabulary instruction. Implications: The results suggest that integrating interactive media into classroom activities can provide a more meaningful and engaging learning experience for students. Keywords: Interactive Media, Vocabulary Learning, English Education, Elementary Students, Learning Engagement Key Findings Highlights Student participation increased during learning activities Vocabulary understanding improved through media interaction Learning atmosphere became more engaging